Pengembangan Screencast Software CAD Untuk Pembuatan Pola Busana - Muslichah, Vammela Mega; Atiqoh, Atiqoh; Walujo, Djoko Adi (Universitas Negeri Malang, 2022)
Distance learning will continue to develop using a variety of effective communication technologies. Overcoming the difficulties of the online learning process for practical materials at LKP Arva School of Fashion, it takes learning media that can be accessed by students anywhere and anytime. This study aims to develop a product in the form of media with a screencast type of pattern making based on the CAD Pattern system, namely Richpeace, to increase the effectiveness of online practical learning. This research method uses ADDIE with the steps of analysis, design, development, implementation and evaluation. This article has only reached the development stage with the final process of media validation based on the responses of media and material experts. From the results of the screencast media trial to students, it was declared valid and feasible and proven to be able to improve students' abilities in making peplum skirt patterns based on CAD pattern making at Arva School of Fashion.AbstrakPembelajaran jarak jauh akan terus berkembang dengan menggunakan beragam teknologi komunikasi yang efektif. Mengatasi kesulitan proses pembelajaran online untuk materi praktik di LKP Arva School of Fashion, dibutuhkan media pembelajaran yang dapat diakses oleh peserta didik dimana pun dan kapan pun. Penelitian ini bertujuan untuk mengembangkan produk berupa media dengan jenis screencast pembuatan pola berbasis CAD Pattern system yaitu Richpeace, untuk meningkatkan efektifitas pembelajaran praktik secara online. Metode penelitian ini menggunakan ADDIE dengan langkah-langkah analisis, desain, pengembangan, implementasi dan evaluasi. Artikel ini hanya sampai pada tahap pengembangan dengan proses terakhir validasi media berdasarkan tanggapan ahli media dan materi. Dari hasil uji coba media screencast ke peserta didik dinyatakan valid dan layak serta terbukti mampu meningkatkan kemampuan peserta didik dalam membuat pola rok peplum berbasis CAD pattern making di Arva School of Fashion.